PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN TERHADAP KINERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERATING PADA PEGAWAI DI KANTOR CAMAT KABUPATEN KERINCI - Yusnita, Ida; Amri, Faisal; Sari, Ayu Esteka (Bussman Journal : Indonesian Journal of Business and Management, 2021)
This study aims to determine the effect of the physical work environment and discipline on employee performance at the Kerinci district office with work motivation as a moderating variable. The population in this study were 55 employees at the Kerinci District Head Office from 3 sub-district offices, namely the Keliling Danau, Sitinjau Laut and Gunung Raya sub-district offices. The sampling technique is full sampling. In this study, there are two stages of analysis that will be carried out, namely First, SEM analysis based on variance (Component based SEM) or Partial Least Square (PLS) with the help of Visual software Smart PLS (Partial Least Square) version 3.0 then with Moderated Structural Equation analysis. Modeling (MSEM). The results showed that the value of the R-Square of performance was 0.543, which means that 54.3% of the variance of the performance variable can be explained by the variables of the physical work environment, discipline and work motivation. The value of the R-Square motivation of 0.219 can be interpreted that 21.9% of the variance of the work motivation variable can be explained by the physical work environment and discipline variables